Ganglionated Plexi Ablation Suppresses Chronic Obstructive Sleep Apnea-Related Atrial Fibrillation by Inhibiting Cardiac Autonomic Hyperactivation - Zhang, Ling; Guo, Yankai; Xiaokereti, Jiasuoer; Cao, Guiqiu; Li, Hongliang; Sun, Huaxin; Li, Kai; Zhou, Xianhui; Tang, Baopeng (Frontiers in Physiology, 2021)
Background-Previous studies have reported that right pulmonary artery ganglionated plexi (GP) ablation could suppress the onset of atrial fibrillation (AF) associated with obstructive sleep apnea (OSA) within one hour. Objective-This study aimed to investigate the chronic effect of superior left GP (SLGP) ablation on AF on a chronic OSA canine model. Methods and Results-Fifteen beagles were randomly divided into three groups: CTRL, OSA, OSA+GP. All the animals were intubated under general anesthesia, and subsequently repeating ventilation-apnea event 4 hours/day, 6 days/week for 12 weeks to establish a chronic OSA model. SLGPs were ablated at the end of 8 weeks. SLGP ablation could attenuate atrial effective refractory period (ERP) reduction, decrease ERP dispersion, window of vulnerability, and AF inducibility. In addition, chronic OSA lead to left atrial (LA) enlargement, left ventricular (LV) ejection fraction decrease, glycogen deposition, and mitophagy, increased necrosis and myocardial fibrosis. SLGP ablation reduced LA sizes and ameliorated LV dysfunction, while the myocardial fibrosis couldn’t be reversed. Additionally, SLGP ablation mainly reduced sympathovagal hyperactivity, post-apnea blood pressure and heart rate rises, decreased the expression of NGF, TH, and CHAT in LA. After SLGP ablation, NOD-like receptor signaling pathway, cholesterol metabolism pathway, and ferroptosis pathway were notably down regulated compared with OSA. Conclusions-SLGP ablation suppressed chronic AF on a chronic Obstructive Sleep Apnea model by sympathovagal hyperactivity inhibition.However, there were no significant changes in myocardial fibrosis.